2020
DOI: 10.1038/s41598-020-63613-4
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking induces human CCR6+Th17 lymphocytes senescence and VEGF-A secretion

Abstract: Chronic exposure to environmental pollutants is often associated with systemic inflammation. As such, cigarette smoking contributes to inflammation and lung diseases by inducing senescence of pulmonary cells such as pneumocytes, fibroblasts, and endothelial cells. Yet, how smoking worsens evolution of chronic inflammatory disorders associated with Th17 lymphocytes, such as rheumatoid arthritis, psoriasis, Crohn's disease, and multiple sclerosis, is largely unknown. Results from human studies show an increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…It has been reported that free radical-induced oxidative stress causes mutations in genetic material and is involved in several neurodegenerative disorders, such as Parkinson's disease and MS. Tobacco increases the risk of autoimmune diseases, such as systemic lupus erythematosus and rheumatoid arthritis, and is associated with other autoimmune disorders like MS [11,12]. Cigarette smoke acts on the cellular level of the immune system, resulting in the development of proinflammatory cytokines [11][12][13]. Smokers have high levels of proinflammatory cytokines (e.g., IL-6), higher levels of C-reactive protein, fibrinogen, and other inflammatory markers [11].…”
Section: Damaging Effects Of Cigarette Smoke On the Immune System In Msmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that free radical-induced oxidative stress causes mutations in genetic material and is involved in several neurodegenerative disorders, such as Parkinson's disease and MS. Tobacco increases the risk of autoimmune diseases, such as systemic lupus erythematosus and rheumatoid arthritis, and is associated with other autoimmune disorders like MS [11,12]. Cigarette smoke acts on the cellular level of the immune system, resulting in the development of proinflammatory cytokines [11][12][13]. Smokers have high levels of proinflammatory cytokines (e.g., IL-6), higher levels of C-reactive protein, fibrinogen, and other inflammatory markers [11].…”
Section: Damaging Effects Of Cigarette Smoke On the Immune System In Msmentioning
confidence: 99%
“…Current cigarette smokers had more severe disease at baseline than never-smokers in terms of Expanded Disability Status Scale score (EDSS) [37]. Exposure to pollutants present in tobacco-related products contributes to the development of proangiogenic and pathogenic CCR6 + Th17 cells [12]. These cells worsen chronic inflammatory disorders, such as MS and rheumatoid arthritis [12].…”
Section: Smoking and Disease Progression In Msmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, telomere shortening and senescence associated with factors such as epigenomic damage, strong mitogen–associated signals and activation of tumor suppressors [ 194 , 202 ]. Smoking and unfavorable environmental factors worsen senescence and the ageing of the whole organism [ 194 , 203 , 204 ]. Moreover, these processes are often linked with chronic stress, diabetes, hypertension, coronary heart disease and other age-related diseases [ 194 , 205 ].…”
Section: Cellular Types Of Stressmentioning
confidence: 99%
“…Chronic inflammation induced by particulate matter exposure triggers T cell senescence, with external stimuli or neighboring senescent cells producing an inflammatory microenvironment (SASP) that reprograms the metabolic machinery of CD8 + T cells by boosting mitochondrial biogenesis, and thus ROS production, distinctively defined as inflamm-aging (339). Cigarette smoke from human studies show an increase in inflammatory CD4+ Th17 lymphocytes at blood-and pulmonary level in smokers (340,341).…”
Section: T Cellsmentioning
confidence: 99%